Choice of treatment for Graves disease - Siti Nurdjanah, Siti Nurdjanah (Universitas Gadjah Mada, 1992)
Gravesdisease is the second common endocrine disease found in the clinic, characterized by hyperthyroidism, ophthalmopathy, diffuse struma with/without dermopathy.CoMmon treatments for hyperthyroidism of Graves disease are anti thyroid drugs, subtotal thyroidectomyorradioiodine (ml). However, reports in the medical literature present widely varying and often conflicting with regard to cure, relapse, frequency aside effects, cost, and compliance. No single form of therapy is acceptable to or suitable for all patients.The choice of treatment should be based upon several factors, such as the age of the patients, the size of the thyroid gland, existence of complications, and other factors.Key Words: Graves disease - hyperthyroidism - antithyroid drugs - thyroidectomy - radioiodine